Pearson discover History book 3 (Karachi: Kifayat Pulishers, 2024)
Pearson Discover History Book 3 offers a comprehensive exploration of world history from the Middle Ages to early modern times. It covers significant events, developments, and civilizations across different regions, including Europe, Asia, Africa, and the Islamic world. The book introduces students to themes such as empire-building, trade routes, religion, warfare, governance, and cultural exchange. Key topics include the rise and fall of empires, medieval societies, the spread of major world religions, the Renaissance, and early exploration. The content is presented through a mix of narratives, timelines, source analysis, and activities designed to promote critical thinking and historical inquiry. With a focus on both global connections and local histories, the book helps students understand how various societies interacted and influenced one another. It builds essential skills such as evaluating evidence, understanding historical context, and making comparisons across time and place. This summary reflects the book$1 (Bs goal of making history accessible, engaging, and relevant for students at the lower secondary level.s
Pearson Discover History Book 3 is part of the engaging and informative Pearson history series designed for lower secondary students. This book continues the journey through key historical themes, time periods, and civilizations, helping students understand how the past has shaped the world today. It is structured to promote critical thinking, inquiry, and historical skills such as analyzing sources, timelines, cause and effect, and continuity and change. The book is aligned with international curriculum standards and includes vivid illustrations, maps, timelines, and primary source excerpts to enhance learning. Each chapter encourages active participation through discussion questions, project work, and assessments. It provides a balanced view of historical events, promoting respect for diverse cultures, societies, and perspectives. Overall, Pearson Discover History Book 3 is a valuable educational resource for developing a strong foundation in history, encouraging curiosity, analysis, and a deeper appreciation of the human story.
Keywords: Medieval Period; Feudalism